Higher education for times of climate crisis – critical awareness, purpose and community. Issue 1 (3rd April 2021) - Phelan, Liam; Lumb, Matt
ABSTRACT: Climate change impacts cascade across scales and sectors, and present specific threats to education institutions and systems, including reduced educational access, participation and attainment by students. In this paper, we set out the pursuit of climate change mitigation and adaptation responses, grounded in commitments to equity and justice, as a renewed fundamental purpose for higher education. To this end, we suggest the understanding of public and private benefits of education that is typically applied to individuals may be usefully applied at institution and system scale. However, in the context of an accelerating climate crisis, adopting a renewed fundamental purpose will require institutions and systems to display critical awareness beyond the public-private benefits divide, towards an understanding of themselves as embedded in – rather than separate to – their broader communities and societies, and an acknowledgement of the particular interests that are foregrounded and privileged in the construction of their purpose.